2018
DOI: 10.1111/1742-6723.12990
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Environmental heatstroke and long‐term clinical neurological outcomes: A literature review of case reports and case series 2000–2016

Abstract: Global temperatures are rising; extreme environmental heat can result in adverse health effects including heatstroke. Acute effects of heat are well recognised, but there is less understanding of potential long-term adverse outcomes. Our aim was to review recent medical literature for clinical cases of environmental heatstroke with a focus on neurological outcome. Structured search strategies were designed to retrieve publications of heatstroke case reports using Ovid Medline and Embase (2000-2016). One thousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
(21 reference statements)
2
18
0
1
Order By: Relevance
“…A decrease in functional status at two years follow up, resulting in the need for elderly institution care, has also been reported in NEHS patients [8] . These outcomes are in line with other studies that have also shown that the cerebellum is particularly susceptible to heat cytotoxicity leading to permanent damage [7,9]. Myocardial dysfunction in HS hospitalized patients has been reported, with elevated cardiac troponin levels representing myocardial damage [10][11][12][13].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…A decrease in functional status at two years follow up, resulting in the need for elderly institution care, has also been reported in NEHS patients [8] . These outcomes are in line with other studies that have also shown that the cerebellum is particularly susceptible to heat cytotoxicity leading to permanent damage [7,9]. Myocardial dysfunction in HS hospitalized patients has been reported, with elevated cardiac troponin levels representing myocardial damage [10][11][12][13].…”
Section: Introductionsupporting
confidence: 90%
“…The combination of heat cytotoxicity and the body's inflammatory and coagulation pathways response leads to multiple organ dysfunction, including encephalopathy, rhabdomyolysis, acute kidney injury, hepatic injury, circulatory failure, cardiac injury and disseminated intravascular coagulopathy (DIC) [3] . In a recent review of persistent neurological impairment in HS patients, Lawton et al found cerebellar dysfunction in 35% of survivors, consisting of cerebellar dysarthria and ataxia, with some patients in a coma for up to two years [7] . A decrease in functional status at two years follow up, resulting in the need for elderly institution care, has also been reported in NEHS patients [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Brain tissue is vulnerable to heat [28]. Almost all patients with HS experienced acute neurological disturbances, and up to 23.3% of the HS patients suffered long-term neurological sequelae [8]. The patterns of neurological deficits included motor dysfunction in 66.7% of the patients, cognitive impairment in 9.5% and both motor and cognitive impairment in 19%.…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of neurological deficits included motor dysfunction in 66.7% of the patients, cognitive impairment in 9.5% and both motor and cognitive impairment in 19%. Long-term cerebellar dysfunction was found in 71.4% of those HS patients [8]. A previous study indicated that AIS was also increased after a critical illness, such as sepsis [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation